1991
DOI: 10.1038/353670a0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of c-jun mediated by MAP kinases

Abstract: The proto-oncogene c-jun is a component of the AP-1 transcription factor family involved in the mediation of nuclear events elicited by extracellular stimuli. The c-jun protein is negatively regulated by phosphorylation of residues near the carboxy terminus which are dephosphorylated in response to phorbol esters. Here we identify two serine residues in the amino terminal A1 transactivation domain which are phosphorylated in response to a variety of mitogens, phorbol esters and activated ras. We present eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
881
6
11

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,393 publications
(924 citation statements)
references
References 18 publications
26
881
6
11
Order By: Relevance
“…ERK1 increases c-Fos expression (Gille et al, 1992) which in turn up-regulates Fra-1 synthesis (Bergers et al, 1995). Additionally, there is evidence, albeit controversial, that indicates that the transactivating potential of cJun is increased by this MAPK (Pulverer et al, 1991;Agarwal et al, 1995;Bogoyevitch et al, 1995). We recently showed that the AP-1 motif at 7184, which was required for elevated u-PAR expression in RKO cells as well as the phorbol ester-inducible expression in GEO cells, was bound with c-Fos, Fra-1, and c-Jun (Lengyel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK1 increases c-Fos expression (Gille et al, 1992) which in turn up-regulates Fra-1 synthesis (Bergers et al, 1995). Additionally, there is evidence, albeit controversial, that indicates that the transactivating potential of cJun is increased by this MAPK (Pulverer et al, 1991;Agarwal et al, 1995;Bogoyevitch et al, 1995). We recently showed that the AP-1 motif at 7184, which was required for elevated u-PAR expression in RKO cells as well as the phorbol ester-inducible expression in GEO cells, was bound with c-Fos, Fra-1, and c-Jun (Lengyel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Since all of these agents increase extracellular signal-regulated kinase (ERK) activity (Fabian et al, 1993;Bogoyevitch et al, 1994;Tsai et al, 1995), the objective of the current study was to determine the role of ERK1 and ERK2 in regulating u-PAR expression in these two colon cancer cell lines. The ERKs, which are mitogen-activated protein kinases (MAPKs), modulate the activity and/or synthesis of a diverse set of transcription factors involved in inducible gene expression (Gille et al, 1992;Rao and Reddy, 1993;Pulverer et al, 1991;Agarwal et al, 1995;Bogoyevitch et al, 1995;Janknecht, 1996;O'Hagan et al, 1996). These MAPKs are activated by phosphorylation on threonine and tyrosine residues by a dual activity kinase MEK1 (Crews et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…c-Jun is part of the activator protein-1 (AP-1) transcription factor, which either exists as Jun homodimer or as a Jun/Fos heterodimer [95]. The transcriptional activity of the AP-1 complex is increased [95] upon phosphorylation of Ser-63 and -73 of c-Jun by JNK [160]. In addition to c-Jun, JNKs also phosphorylate other AP-1 proteins, including JunB and JunD [25,95].…”
Section: Map Kinase Signalingmentioning
confidence: 99%
“…The phosphorylated ERKs activate other signaling proteins such as cPLA 2 (Nemeno et al, 1993;Lin et al, 1993) as well as other kinases (Boulton et al, 1991;Sturgill et al, 1988;Stokoe et al, 1992). In addition, the phosphorylated ERKs translocate to nucleus (Chen et al, 1992;Seth et al, 1992;Sanghera et al, 1992;Lenormand et al, 1993) where they activate transcription factors such as TCFs through phosphorylation (Alvarez et al, 1991;Pulverer et al, 1991;Baker et al, 1992;Gille et al, 1992) which leads to the activation of speci®c genes involved in cell proliferation (Davis, 1992;Johnson and Vaillancourt, 1994).…”
Section: Map Kinase Kinase-1 and Map Kinase Kinase-2mentioning
confidence: 99%